Analysis of discriminatory game variables between winners and losers in women's handball world championships from 2007 to 2017 - de Paula, L. V.; Costa, F. E.; Ferreira, R. M.; Menezes, R. P.; Werneck, F. Z.; Coelho, E. F.; Greco, P. J (Kinesiology, 2020)
The aim of this study was to identify game variables that discriminated winning from losing teams and to understand how these variables contributed to victory by observing goal differences in matches of the women`s handball world championships. The sample comprised 471 WCh`s games played between 2007 and 2017. The games were grouped into three clusters: balanced games - difference of 1-8 goals; unbalanced games - difference of 9-20 goals; and very unbalanced games - difference of > 20 goals. Generally, the performance of winning teams was significantly higher (in most variables), or lower in the case of the number of technical faults (p<.05). In the balanced games, there was a greater contribution of defensive variables (stolen balls, blocked throws, and goalkeeper`s efficiency indicators) in relation to attack variables (attack efficiency and throw efficiency indicators). For victory, the number of technical faults reduce the chances of winning. Games with the unbalanced and very unbalanced goal differences seem to follow the same tendency; however, in the very unbalanced games, there were more assists, yellow cards and 2-min suspensions. We concluded that the decisive variables for victory in the balanced games showed a greater weight, with a special emphasis on stolen balls followed by offensive variables (throw efficiency indicators, attack efficiency, and technical faults). There was an equal tendency for the games with unbalanced and very unbalanced outcomes.